2021
DOI: 10.1007/s10753-021-01464-5
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Exaggerated Cytokine Production in Human Peripheral Blood Mononuclear Cells by a Recombinant SARS-CoV-2 Spike Glycoprotein S1 and Its Inhibition by Dexamethasone

Abstract: An understanding of the pathological inflammatory mechanisms involved in SARS-CoV-2 virus infection is necessary in order to discover new molecular pharmacological targets for SARS-CoV-2 cytokine storm. In this study, the effects of a recombinant SARS-CoV-2 spike glycoprotein S1 was investigated in human peripheral blood mononuclear cells (PBMCs). Stimulation of PBMCs with spike glycoprotein S1 (100 ng/mL) resulted in significant elevation in the production of TNFα, IL-6, IL-1β and IL-8. However, pre-treatment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 47 publications
1
44
0
Order By: Relevance
“…With respect to immune responses induced by SARS-CoV-2 infection, it is now established that this may involve an exaggerated inflammation, also known as cytokine storm [33-35]. Recently, we reported induction of increased release of pro-inflammatory cytokines in human peripheral blood mononuclear cells stimulated with a recombinant SARS-CoV-2 spike protein sub-unit S1, further confirming the role of the spike protein in COVID-19 cytokine storm [36].…”
Section: Discussionmentioning
confidence: 71%
“…With respect to immune responses induced by SARS-CoV-2 infection, it is now established that this may involve an exaggerated inflammation, also known as cytokine storm [33-35]. Recently, we reported induction of increased release of pro-inflammatory cytokines in human peripheral blood mononuclear cells stimulated with a recombinant SARS-CoV-2 spike protein sub-unit S1, further confirming the role of the spike protein in COVID-19 cytokine storm [36].…”
Section: Discussionmentioning
confidence: 71%
“…Finally, we tested 3 investigational therapies previously predicted as potentially effective in SARS-CoV-2 infection, including sirolimus ( 25 , 26 ), metformin ( 27 29 ), and β-D-N 4 -hydroxycytidine (N-hydroxycytidine) ( 30 ). We found that sirolimus was highly effective in reducing virus titer in tissues from 3 donors but did not significantly affect titers in 2 donors or Vero cells ( Figure 4D ).…”
Section: Resultsmentioning
confidence: 99%
“…Dexamethasone is a corticosteroid and proven therapy for SARS-CoV-2 infection ( 22 , 23 ). The mechanism of action of dexamethasone that improves the outcome of SARS-CoV-2 infection is not empirically established but is thought to be attenuation of inflammation ( 24 , 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a review by Hariharan et al (2021) suggests that inhibition of NF-B activation, with the resultant reduction in exaggerated production of pro-inflammatory cytokines like TNF will potentially result in a reduction in cytokine storm in severe COVID-19. Our recent studies also showed that NF-B activation is a mechanism for SARS-CoV-2 spike protein S1-induced exaggerated production of TNF, IL-6, IL-1β and IL-8 in PBMCs (Olajide et al, 2021). The seed extract of Garcinia kola and garcinoic acid inhibited both cytoplasmic activation, DNA binding and transcriptional activity of NF-B in SARS-CoV-2 spike protein S1-simulated PBMCs, suggesting a role for the transcription factor in their anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly, studies have shown that the spike glycoproteins, especially the S1 sub-unit are also a target for the host immune responses (Merad et al, 2020). Recent studies have confirmed that the S1 sub-unit induced inflammation in immune cells through activation of cellular inflammatory signalling pathways (Shirato and Kizaki, 2021;Olajide et al, 2021).…”
Section: Introductionmentioning
confidence: 99%